PENINGKATAN HASIL BELAJAR MURID PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE (TPS) DI KELAS V SD NEGERI 05 PASAMAN - Nanda, Rahma; Shilfia Iraqi, Hana; Zuryanty, Zuryanty; Zahara, Leni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students due to the lack of learning activities that actively involved them in the learning process, as the instruction was still teacher-centered. The purpose of this study was to describe the improvement of students’ learning outcomes in Science and Social Studies (IPAS) learning through the implementation of the Think Pair Share (TPS) cooperative learning model in Grade V of SD Negeri 05 Pasaman, Kabupaten Pasaman Barat. This study employed Classroom Action Research (PTK) using qualitative and quantitative approaches, conducted in two cycles consisting of planning, implementation, observation, and reflection stages. Data were collected through test and non-test techniques. The research subjects included the classroom teacher as the observer, the researcher as the practitioner, and 28 students consisting of 13 male students and 15 female students. The findings showed improvements in every observed aspect. The Deep Learning Lesson Plan (RPPM) in Cycle I obtained an average score of 83.33% (Good) and increased to 95.83% (Very Good) in Cycle II. Teacher and student activities also improved from an average of 82.5% to 90% (Very Good). Students’ learning outcomes increased from an average score of 75.71 (Fair) in Cycle I to 89.10 (Good) in Cycle II. Therefore, the TPS model was proven effective in improving learning outcomes in the IPAS subject.